Chronological horizon of Weichselian submoraine organic formation and macrofossil finds with radiocarbon and tree-ring δ18O analyses - Oinonen, Markku; Arppe, Laura; Uusitalo, Joonas; Helama, Samuli; Nöjd, Pekka; Mäkinen, Harri; Saranpää, Pekka; Mizohata, Kenichiro (Elsevier, 2026)
Detailed chronological assessment has been performed on a strongly compressed submorainic organic layer found from a river valley in the Lemmenjoki area, Northern Finland, by using 14C and δ18O analyses. Clear effect of reworked carbon from above has been observed within the basal part of the layer. The radiocarbon data combined with existing chronological information suggest that the layer was deposited during the Marine Isotope Stage 3 (MIS3), supporting the previously published interpretation. Particularly, most of the dates are indistinguishable from the 14C background level, indicating their association with the early phase of MIS3 time period. Oxygen isotopic data resembles the data from the last 400 years within the eastern Fennoscandia, suggesting similar growth conditions during the period compared to modern era.
Keywords: Northern Finland; Weichselian; peat formation; radiocarbon; oxygen isotopes; chronology; marine isotope stages